A strategy for promoting lipid production in green microalgae Monoraphidium sp. QLY-1 by combined melatonin and photoinduction. (July 2017) - Li, Dafei; Zhao, Yongteng; Ding, Wei; Zhao, Peng; Xu, Jun-Wei; Li, Tao; Ma, Huixian; Yu, Xuya
Graphical abstract: Highlights: Lipid content of QLY-1 increased by 1.32-fold under photo-melatonin induction. Influence of melatonin on microalgal physiology was investigated. ROS and lipid biosynthesis-related enzyme were related to lipid accumulation. The strategy could be developed for efficient microalgal lipid production. Abstract: Microalgae lipids are potential candidates for the production of renewable biodiesel. The combination of plant hormones and two-step cultivation regulates lipid production in microalgae. A strategy for promoting lipid accumulation in Monoraphidium sp. QLY-1 by combining exogenous melatonin (MT) and photoinduction was developed. The effects of melatonin on the lipid content, reactive oxygen species (ROS), and activities of three key fatty acid biosynthetic enzyme in Monoraphidium sp. QLY-1 were investigated. The lipid content increased by 1.32-fold under 1 μM melatonin treatment. The maximum lipid content achieved was 49.6%. However, the protein and carbohydrate contents decreased rapidly from 57.21% to 47.96% and from 53.4% to 37.71%, respectively. Biochemical and physiological analyses suggested that the ROS and lipid biosynthesis-related enzyme activities correlated with increased lipid accumulation under photo-melatonin induction conditions.